Long-term Effect of the β2-Receptor Agonist Procaterol on Daily Life Performance and Exercise Capacity in Patients with Stable Chronic Obstructive Pulmonary Disease - Shioya, Takanobu; Satake, Masahiro; Sato, Kazuhiro; Sano, Masa-aki; Sugawara, Keiyu; Takahashi, Hitomi; Honma, Mitsunobu (Arzneimittelforschung, 2008)
The present study was undertaken to evaluate the long-term effect of procaterol hydrochloride (CAS 62929-91-3, Meptin™), a third generation β2-receptor agonist on lung function, exercise capacity, health-related quality of life (HRQOL) and activities of daily living (ALDs) in patients with stable chronic obstructive pulmonary disease (COPD). Twenty patients were randomly assigned to the procaterol group or to the control group, who received oxitropium bromide (CAS 30286-75-0), an anticholinergic agent. Procaterol was inhaled three times a day at a dose of 20 µg, while oxitropium was inhaled three times a day at a dose of 200 µg. The subjects were evaluated based on spirometry, exercise capacity, the Borg Scale, HRQOL, and ADLs before and after 12, 24 and 52 weeks of therapy. The values of forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), total lung capacity (TLC), functional residual capacity (FRC), residual volume (RV), maximal inspiratory pressure (PImax), and maximal expiratory pressure (PEmax) were significantly improved at 12, 24 and 52 weeks compared with baseline values in the procaterol group (p<0.05, p<0.01), while these values did not differ from baseline values at any point in the oxitropium group (p>0.05). Additionally, 6-min walking distances and Borg Scale values showed significant improvement at 12, 24 and 52 weeks compared with baseline values in the procaterol group (p<0.05, p<0.01), but did not significantly differ from baseline values in the oxitropium group at any point (p>0.05). Likewise, the scores for dyspnea, fatigue, emotional function, mastery, total scores and ADLs were significantly higher at 12, 24 and 52 weeks compared with the baseline values in the procaterol group (p<0.05, p<0.01), but did not differ at any point in the oxitropium group (p>0.05). These results suggest the effectiveness of long-term regular bronchodilator therapy with the β2-receptor agonist procaterol in patients with stable COPD.
Keywords: β2-Receptor agonists; CAS 62929-91-3; Meptin™; Procaterol hydrochloride, activities of daily living, effects on lung function; exercise capacity, health-related quality of life